Hubungan Tadarus Al-Qur’an dengan Daya Ingat Siswa - Yuhana; Muhamad Fauzi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to determine the relationship between the habit of reciting the Qur'an and the memory of students at Syabab Al-Fatih Junior High School. The focus of the study is to examine the effect of regular Qur'an recitation on students' memory, particularly their memorization of Qur'anic verses, as a response to poor memory caused by technological developments and declining religious activities. This study used a quantitative approach with non-probability sampling, namely saturated sampling, in which the entire population of 37 students was used as a sample in accordance with the principle of saturated sampling commonly used for populations of less than 100 people (Arikunto). Data were collected through observation, questionnaires, and documentation, then analyzed using validity, reliability, normality, and product moment correlation tests to examine the relationship between the variables of Quran recitation and students' memory. According to Saihu, as quoted by Fathor Rozi, the ritual of reciting the Qur'an aims to instill and maintain students' memory, especially as reinforcement for memorizing juz 30. The results of the study showed a positive and significant relationship between Quran recitation and students' memory, with a Pearson correlation coefficient of 0.835 (very strong category) and a p-value of 0.000. These findings confirm that the more often students recite the Quran, the better their memory skills, especially in remembering the Quranic recitation.